Awe Guards My Creativity: The Interactive Effect of Perceived Abusive Supervisory Behavior, Dispositional Awe, and Creative Self-Efficacy on Chinese Employee Creativity - Atamba, Cynthia; Popelnukha, Anastasia; Ibrahim, Farida Lukoko (Frontiers in Sociology, 2020)
The study examined the responses of employees to supervisors who exhibited abusive behavior and invoked dispositional awe to influence their followers. The proposition is that two divergent predictors of supervisor effectiveness interact to affect the behavior of subordinates. The purpose of this study was to examine the interactive effect of perceived abusive supervisory behavior and perceived supervisor dispositional awe on employee creative self-efficacy and creativity. To test the proposed model, we collected cross-sectional data from 196 working professionals pursuing their Masters of Business Administration (MBA) at a large university in China. Our findings confirmed that perceived abusive supervisory behavior and perceived supervisor dispositional awe were predictors of employee creativity. Also, perceived supervisor dispositional awe moderated the relationship between perceived abusive supervisory behavior and employee creative self-efficacy. The theoretical and practical implications for leaders and organizations were discussed.